2021
DOI: 10.1111/jcmm.17016
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant preservation conditions for mesenchymal stem/stromal cells derived from perinatal and adult tissue sources

Abstract: The interplay between mesenchymal stem/stromal cells (MSCs) and preservation conditions is critical to maintain the viability and functionality of these cells before administration. We observed that Ringer lactate (RL) maintained high viability of bone marrow–derived MSCs for up to 72 h at room temperature (18°C–22°C), whereas adipose‐derived and umbilical cord‐derived MSCs showed the highest viability for 72 h at a cold temperature (4°C–8°C). These cells maintained their adherence ability with an improved rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 62 publications
(114 reference statements)
0
12
0
Order By: Relevance
“…UC-MSCs are potential allogeneic cells for the treatment of cardiovascular disease, as they are “ready to use” and easy to isolate, they rapidly proliferate, and they secrete hepatocyte growth factors, 322 which are involved in cardioprotection and cardiovascular regeneration. 323 The pilot study using UC-MSCs in 30 patients with heart failure, called the RIMECARD trial, was the first reported trial for which the results supported the effectiveness of UC-MSCs, as seen in the improved ejection fraction, left ventricular function, functional status, and quality of life in patients administered UC-MSCs.…”
Section: Msc Applications In Cardiovascular Disease: a Promising But ...mentioning
confidence: 99%
See 1 more Smart Citation
“…UC-MSCs are potential allogeneic cells for the treatment of cardiovascular disease, as they are “ready to use” and easy to isolate, they rapidly proliferate, and they secrete hepatocyte growth factors, 322 which are involved in cardioprotection and cardiovascular regeneration. 323 The pilot study using UC-MSCs in 30 patients with heart failure, called the RIMECARD trial, was the first reported trial for which the results supported the effectiveness of UC-MSCs, as seen in the improved ejection fraction, left ventricular function, functional status, and quality of life in patients administered UC-MSCs.…”
Section: Msc Applications In Cardiovascular Disease: a Promising But ...mentioning
confidence: 99%
“…320 A 3-year follow-up report from the MyStromal-Cell Trial confirmed that patients who received AT-MSC administration maintained their preserved exercise capacity and their cardiac symptoms improved, whereas the control group experienced a significant reduction in exercise performance and a worsened cardiovascular condition. 321 UC-MSCs are potential allogeneic cells for the treatment of cardiovascular disease, as they are "ready to use" and easy to isolate, they rapidly proliferate, and they secrete hepatocyte growth factors, 322 which are involved in cardioprotection and cardiovascular regeneration. 323 The pilot study using UC-MSCs in 30 patients with heart failure, called the RIMECARD trial, was the first reported trial for which the results supported the effectiveness of UC-MSCs, as seen in the improved ejection fraction, left ventricular function, functional status, and quality of life in patients administered UC-MSCs.…”
Section: Msc Applications In Cardiovascular Disease: a Promising But ...mentioning
confidence: 99%
“…The study showed that no serious adverse events or adverse events occurred in the patients. Women reported satisfaction with their sex lives; however, there was no significant change in AMH, FSH and estradiol levels (Nguyen T. et al, 2021).…”
Section: Msc Therapy For Female Reproductive Disorders: Clinical Trialsmentioning
confidence: 87%
“…Cells exhibit altered cellular functions leading to decreased regenerative bioactivity with increasing age (Peffers et al, 2016;Marędziak et al, 2016;Y.-H. K. Yang 2018). In addition, the authors have demonstrated that long-term type II diabetes mellitus could induce remarkable changes in mtDNA genetic profiles and negatively interfere with cell metabolism and bioactivity (Nguyen T. et al, 2021). On the other hand, potential genetic changes in the reproductive system need to be considered when allogenic cells are applied for the management of reproductive health (X.…”
Section: Using Autologous Versus Allogenic Ascs: Pros and Contrasmentioning
confidence: 99%
See 1 more Smart Citation